The Development of the GeolISSTerm Terminological Dictionary - Stanković, Ranka; Trivić, Branislav; Kitanović, Olivera; Blagojević, Branislav; Nikolić, Velizar (Infotheca - Journal for Digital Humanities; Vol 12 No 1 (2011): Infotheca - Journal of Informatics and Librarianship, 2024)
This paper presents the structure and implementation of the electronic dictionary of geologic terms (GeolISSTerm) as a special-purpose taxonomy of basic geologic concepts and terms. GeolISSTerm can be an elementary electronic resource in the process of domain formation in the Geologic Information System of Serbia (GeolISS). As such, it is the core of GeolISS through which validation, classification and specification of attributes of the observed and the interpreted takes place. GeolISSTerm is a result of the work on the project The Development of Geologic Terminology and Nomenclature for the Geologic Database of Serbia carried out by the Faculty of Mining and Geology, University of Belgrade, funded by the Ministry of the Environment and Spatial Planning of the Republic of Serbia. A short history of GeolISSTerm and an overview of the structure and the way of arranging terms, in view of the terminological resources and the position of the GeolISSTerm dictionary in the semantic spectrum is followed by a description of the approach to the development of the geologic terminology and the structure of the vocabulary using the UML (Unified Modeling Language) model. The concept of domain control in the Geologic Information System of Serbia has been explained in detail. Software solutions for browsing and searching the dictionary online and the solution for domain control, namely, integration into GeolISS are illustrated by screenshots of the interface. The possibilities of exporting the vocabulary to standard ontology languages, such as the OWL, modelled on the GeoSciML initiative are planned to be provided. The electronic edition of the dictionary is complemented by the printed version.